Public Value Management: A Case Study of Transitional Change in Disability Sector Reform in Western Australia. Issue 2 (17th March 2016) - Edwards, Mark G.; Soo, Christine; Greckhamer, Thomas
Abstract : This paper contributes to the study of public value management (PVM). PVM is distinguished from other approaches to public administration in its focus on establishing community networks and collaborative capacity building for the creation of public value. We explore PVM through a case study of a public–community sector partnership strategy called the positive behaviour framework (PBF), a state government initiative designed to transform services for people with disabilities. The development and implementation of the PBF is analysed via a transitional change or 'sector awareness' model. Each phase of the model is illustrated through 'positive stories' that depict key moments in the change process and in the activities that public sector managers employed to raise awareness, build capacity, and promote collaboration. We discuss the implications of the study for disability sector change management and for the further study of the PVM approach to public sector administration. Abstract : This paper contributes to the study of Public Value Management (PVM). We explore PVM through a case study of a public‐community sector partnership strategy. We discuss the implications of the study for disability sector change management and for the further study of the PVM.